Menu Close

Simplify-2-2-2-2-2-2-2-




Question Number 146964 by mathdanisur last updated on 16/Jul/21
Simplify:  (((√2) ∙ (√(2 + (√2))) ∙ (√(2 - (√2))))/( (√(2(√2))))) = ?
Simplify:22+22222=?
Answered by Olaf_Thorendsen last updated on 16/Jul/21
x = (((√2)(√(2+(√2))).(√(2−(√2))))/( (√(2(√2)))))  x = (((√2)(√((2+(√2))(2−(√2)))))/( (√(2(√2)))))  x = (((√2)(√2))/( (√(2(√2))))) = (2/( (√(2(√2))))) = ((2(√(2(√2))))/(2(√2))) = (√(√2)) = 2^(1/4)
x=22+2.2222x=2(2+2)(22)22x=2222=222=22222=2=214
Commented by mathdanisur last updated on 16/Jul/21
thank you Ser
thankyouSer

Leave a Reply

Your email address will not be published. Required fields are marked *